Jean-Marie Guyau notre contemporain - Contini, Annamaria; Riba, Jordi (La croisée des chemins, 2023)
The philosophy of life according to Jean-Marie Guyau (1854-1888) offers one of the most original perspectives of his time in the fields of ethics, aesthetics and sociological studies. However, despite his influence on authors such as Nietzsche, Bergson, Durkheim and Kropotkin, he has been deemed of little importance in the history of French philosophy. This book, to which the greatest specialists of Guyau have contributed, aims to rediscover the relevance of his thought, by asking a fundamental question: who are Guyau's true contemporaries? Is Guyau merely an author of the second half of the 19th century, whose work was completed by Nietzsche and Bergson; or, on the contrary, is his work of a topicality that was not sufficiently acknowledged at the time and that belongs, from a conceptual point of view, to our 21st century? The book is intended both for specialists in nineteenth-century French philosophy and, more generally, for anyone interested in non-linear and unconventional philosophical itineraries.